VIII przykazanie Dekalogu na tle koncepcji świadectwa i świadka w tekstach legislacyjnych Starego Testamentu - Stefański, Jacek (Verbum Vitae, 2015)
The Eighth Commandment forbids bearing false witness, which falls under the general category of lying. Why, then, does the Decalogue not forbid lying overall? A thorough analysis of the Eighth Commandment sheds light on the problem: deceitful speech is primarily an act against God who has revealed Himself as the God of truth, always faithful to His word. In this way lying becomes similar not only to the Second Commandment regarding taking the Lord’s name in vain, but even to the profanation of the Sabbath. After all, keeping the Lord’s Day holy is a testimony to the Creator’s authority over creation. Since man was created in the image and likeness of God who is the source of all truth, any use of deceitful speech distorts the image of God, which one bears in himself. Such distortion always constitutes a false testimony (bearing false witness) to the perfection and truthfulness that characterize all of God’s actions, including His work of creation. Moreover, when a member of the Covenant community bears false witness against his neighbor, his deceitful speech is all the more deplorable, because he both distorts the image of the Creator in himself and also shatters the sacred trust which flows from the bond upon which the people of God rely in their daily dealings with one another. The harsh consequences and penalties imposed against those who bear false witness stand as a testimony to the seriousness of destroying the sacred covenantal trust between God and man when lying takes place. In a way, every truth is a reflection of the Lord who is the Divine Truth. With St. Thomas Aquinas one can say that every truth-telling shows reverence for our Lord Jesus Christ who is the Way, the Truth and the Life.